Litoribacterium kuwaitense gen. nov., sp. nov., isolated from a Kuwait tidal flat. Issue 4 (28th April 2021) - Mahmoud, Huda; Eapen, Susan; Al-Bajjali, Fatimah; Al-Qattan, Anwar; Jose, Liny
Abstract : A Gram-stain-positive, strictly aerobic, spore-forming, rod-shaped and non-motile bacterium designated strain SIJ1 T was obtained from tidal flat sediment collected from the northern shore of Kuwait Bay, northwest of the Arabian Gulf. Strain SIJ1 T grew optimally at 30 °C and pH 7–8 in the presence of 6 % (w/v) NaCl. The cell-wall peptidoglycan was based on meso -diaminopimelic acid and an unsaturated menaquinone with seven isoprene units (MK-7) was the predominant respiratory quinone. It contained anteiso-C15 : 0, iso-C16 : 0 and iso-C15 : 0 as the major fatty acids and ribose as the major whole-cell sugar. The polar lipids were diphosphatidylglycerol, phosphatidylglycerol, unidentified phospholipid, an unidentified glycolipid, phosphoglycolipid and an unidentified lipid. Phylogenetic analysis based on 16S rRNA genes revealed that SIJ1 T showed a distinct evolutionary lineage within the Firmicutes. The DNA G+C content was 43.1 mol% and the full genome analysis for strain SIJ1 T showed that it had a genome size of 3 989 945 bp and contained 4085 predicted protein-encoding genes. The SIJ1 T annotated genome showed more stress resistance encoding genes in comparison to its closely related strains. The amino acid identity and average nucleotide identity data for the whole genome proved that strain SIJ1 T does indeed represent a novel genus. The strain was distinguishable from the phylogenetically related genera through differences in several phenotypic properties. On the basis of the phenotypic, phylogenetic and genetic data, strain SIJ1 T represents a novel genus and species in the family Bacillaceae, for which the name Litoribacterium kuwaitense gen. nov., sp. nov. is proposed. The type strain is SIJ1 T (=DSM 28862 T =LMG 28316 T ).